2017
DOI: 10.1176/appi.ajp.2016.16060721
|View full text |Cite
|
Sign up to set email alerts
|

Temporal, Diagnostic, and Tissue-Specific Regulation of NRG3 Isoform Expression in Human Brain Development and Affective Disorders

Abstract: Objective Genes implicated in schizophrenia are enriched in networks differentially regulated during human CNS development. Neuregulin 3 (NRG3), a brain-enriched neurotrophin, undergoes alternative splicing and is implicated in several neurological disorders with developmental origins. Isoform-specific increases in NRG3 are observed in schizophrenia and associated with rs10748842, a NRG3 risk polymorphism, suggesting NRG3 transcriptional dysregulation as a molecular mechanism of risk. The authors quantitativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 54 publications
2
38
0
Order By: Relevance
“…Similarly, in human brain, genomic regions associated with schizophrenia are enriched for genes that show differential isoform usage across neurodevelopment 7 , implicating many schizophrenia-associated risk loci in the regulation of the expression of specific RNA transcripts. Consistent with these findings, examples of associations between psychiatric risk-associated loci and the abundance of novel, alternatively spliced transcripts are beginning to emerge [8][9][10] , complementing numerous reports of altered splicing patterns in the brains of psychiatric cases, compared to controls [11][12][13] .…”
Section: Introductionmentioning
confidence: 69%
“…Similarly, in human brain, genomic regions associated with schizophrenia are enriched for genes that show differential isoform usage across neurodevelopment 7 , implicating many schizophrenia-associated risk loci in the regulation of the expression of specific RNA transcripts. Consistent with these findings, examples of associations between psychiatric risk-associated loci and the abundance of novel, alternatively spliced transcripts are beginning to emerge [8][9][10] , complementing numerous reports of altered splicing patterns in the brains of psychiatric cases, compared to controls [11][12][13] .…”
Section: Introductionmentioning
confidence: 69%
“…Increased levels of Nrg3 led to the opposite result with a decrease in glutamatergic neurotransmission. These observations provide one mechanism to explain how alterations in Nrg3 mRNA levels (Kao et al, ; Paterson et al, ) underlie changes in glutamatergic neurotransmission associated with these pathological conditions (Cappellini et al, ; Gao & Penzes, ).…”
Section: Introductionmentioning
confidence: 99%
“…Neuregulin-3 (Nrg3) is a member of the neuregulin (Nrg1-4) family of growth factors, which play important roles in the developing and mature nervous system (Birchmeier & Bennett, 2016;Grieco, Holmes, & Xu, 2018;Mei & Nave, 2014;Mei & Xiong, 2008). Nrg3 is of particular interest as it has emerged as a candidate risk gene for several neuropsychiatric disorders including bipolar disorder and schizophrenia (SZ) (Avramopoulos, 2018; P. L. Chen et al, 2009;Hayes et al, 2016;Loos et al, 2014;Paterson et al, 2017). Recent studies have also indicated that Nrg3 plays important roles in cortical development (Bartolini et al, 2017) and glutamatergic neurotransmission (Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complementary to the previous tissue-specific analysis, this clustering approach allowed us to identify an lncRNA (RLOC_00033166) expressed in all nervous system tissues with a mean TPM = 7.89 but not detected in any other tissues. Interestingly, this lncRNA is transcribed in antisense orientation to the Neuregulin 3 gene (NRG3), which is involved in neuroblast cell differentiation 30…”
Section: Landscape Of Canine Lncrna Transcriptionmentioning
confidence: 99%